PENERAPAN MODEL PEMBELAJARAN MORDISCVEIN BERBANTUAN MAGIC BOX DALAM MENINGKATKAN HASIL BELAJAR IPA DI SEKOLAH DASAR KOTA GORONTALO - Saleh, Meylan; Hasim, Evi; Bin Smith, Mardiah (Journal of Education and Teaching Learning, 2024)
This research aims to apply the Mordiscvein learning model assisted by a magic box in improving science learning outcomes in Gorontalo City elementary schools. The type of research used is classroom action research which consists of 2 cycles. In the initial observation, the student learning outcomes obtained were still very low, from 20 students who completed only 8 students or 40% and 12 students who did not complete or 60%. After carrying out the first cycle of action, there was an increase in the initial observation data, but it had not yet reached the specified success indicators. Of the 18 students, 11 students completed or 61%, while 7 students or 39% did not complete. After cycle II there was an increase in student learning outcomes, of the 18 students there were 16 students who completed it or 89% while 2 students did not complete it or 11%. Based on the research results, it can be concluded that the application of the Mordiscvein learning model assisted by the Magic Box can improve student learning outcomes in science lesson content in class V in Gorontalo City.